Palladium thin films on microfiber filtration paper as flexible substrate and its hydrogen gas sensing mechanism. (21st June 2019) - Shahzamani, Zahra; Ranjbar, Mehdi; Comini, Elisabetta; Goodarzi, Mehdi Torabi; Salamati, Hadi; Sberveglieri, Giorgio
Abstract: Cost-effective, simple and flexible hydrogen gas sensors operating at room temperature were demonstrated based on DC magnetron sputtered palladium thin films. The main idea is to use commercial microfiber filtration paper as a cheap, fibrous and flexible substrate for palladium. With this objective, Pd thin films with 21, 38 and 54 nm thicknesses were deposited and characterized by grazing incident X-ray diffraction (GIXRD) and scanning electron microscope (SEM). The gas sensing behavior was tested by hydrogen gas in the concentration rang of 0.5–10%. GIXRD showed a PdX/Pd phase and SEM revealed existing of many structural nanocracks. An activation process was needed where sensors were heated up to 110 °C in the presence of 10% H2 . Then a desirable hydrogen sensitivity with good stability based on hydrogen induced lattice expansion (HILE) effect in which conductance increases was observed. However, for low Pd thicknesses (21 and 38 nm) and at below 4% H2, an inverse effect was observed in which the conductance decreased instead of increasing. For all samples the response time is incremental in the range of 0.5–4% and declining for 4–10%. Moreover, the deposited Pd sensors operate well when they are bent inward or outward. The governed physical mechanism was expressed and discussed. Highlights: Pd thin films were deposited on microfiber filtration paper by DC sputtering method. Their hydrogen sensing properties were examined for different Pd thicknesses. Sensing mechanisms including invers and direct current responses were observed. The stability of sensing response of fabricated sensors was examined. The response to bending in presence and absence of gas was investigated.